XFEM based analysis of fatigue crack growth in damaged wing-fuselage attachment lug. (May 2020) - Solob, A.; Grbović, Aleksandar; Božić, Ž.; Sedmak, S.A.
Highlights: Numerical investigation of fatigue life of damaged wing-fuselage attachment lug. Insertion of the corner cracks to the FE model of the lug which was not done before. Comparison of the corner crack growth and through crack growth in the attachment lug. Very good agreement of the fatigue life values obtained with XFEM and FEM. High applicability of results in the aircraft maintenance business. Abstract: The research presented in this paper is based on the use of extended finite element method (XFEM) for stress intensity factors (SIFs) determination in the case of fatigue crack presented in the wing-fuselage attachment lug used in light aerobatic aircraft. The presence of the through crack at the attachment lug hole is not allowed since its growth due to high dynamic loads is usually fast and can lead to catastrophic consequences. To demonstrate how dangerous the appearance of the crack could be, as well as to estimate the residual strength and fatigue life of cracked component, finite element model of attachment lug was made, and analyses were carried out using the maximum load that can occur during the flight (load factor n = 6). The predicted number of cycles to complete failure was – as expected – low, confirming the fact that attachment lugs must be designed using safe-life approach.